Numerical Optimization for the Impact Performance of a Rubber Ring Buffer of a Train Coupler - Ping Xu; Chengju Qu; Shuguang Yao; Chengxing Yang; Ao Wang (Machines, 2021)
Shock and vibration caused by mechanical motion bring huge potential threats to the service life and assembly reliability of mechanical systems. Rubber materials have been widely used in aircraft, trains, and other engineering fields, due to their excellent properties in shock and vibration absorption. This paper aimed to study the rubber ring buffer applied to a certain type of Chinese locomotive. Firstly, the finite element model was established and verified through experimental data. Based on the verified simulation model, the influence of the constitutive parameters (C01/C10 ratio height H and contour radius R) of the rubber ring on its energy absorption and peak crushing force under impact loading was studied in a numerical environment. Finally, the design of the experiment was carried out by the optimized Latin hypercube method, and the response surface model was established, which intuitively demonstrated the influence of the relevant parameters of the rubber ring on the change trend of the energy absorption and peak force. Based on the proxy model, the parameters that improve the crashworthiness of the rubber ring buffer were found quickly by the NSGA-II optimization algorithm, and the problems of a long calculation time and low optimization efficiency when using the conventional finite element method were avoided. The optimization results stated that when H = 107.57 mm and R = 85.70 mm, C01/C10 = 0.0571 of the energy absorption of the optimized buffer was increased by 59.03%, and the peak force was decreased by 14.37%, compared with the original structure. The optimized rubber ring buffer is expected to reduce the peak crushing force, enhance the energy absorption capacity, and mitigate the damage to the train system caused by shock and vibration.